2021
DOI: 10.1029/2020gl092263
|View full text |Cite
|
Sign up to set email alerts
|

The Ocean Carbon Response to COVID‐Related Emissions Reductions

Abstract: The socioeconomic disruptions associated with the COVID-19 pandemic have caused an unprecedented drop in global emissions of carbon dioxide (CO 2) and other atmospheric pollutants. The year 2020 was characterized by a 6.4% decrease in global CO 2 emissions relative to the previous year (Carbon Monitor Project, 2021; Liu et al., 2020), with average daily emissions declines peaking at −26% in individual countries (Le Quéré et al., 2020). The duration and severity of the emissions decline in the future is as yet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…However, it does match the bottom-up emissions shown in Fig. 4A (13) reasonably well through November 2020 (26).…”
Section: Co 2 and Ch 4 Atmospheric Growth Ratesmentioning
confidence: 75%
“…However, it does match the bottom-up emissions shown in Fig. 4A (13) reasonably well through November 2020 (26).…”
Section: Co 2 and Ch 4 Atmospheric Growth Ratesmentioning
confidence: 75%
“…This uncertainty is due both to the forced response of the ocean and to interannual variability. Lovenduski et al (26) found that, for a change in ocean carbon uptake to be observable with our current network of ocean buoy measurements, it would need to be four times larger than the COVID-19 emissions reductions. This will be a challenge as we work to quantify the effect of future permanent CO2 emissions reductions on atmospheric CO2 mixing ratios.…”
Section: Covid-19 Equivalent Nox Emissions Year By Countrymentioning
confidence: 77%
“…[2021] and mimics the approach for the detection of a climate change signal in real-world observations [Bindoff and Stott, 2013]. The resulting correlation coefficients are shown in the subplots of Figure 1, where small circles show the set of 30 Pearson's correlation coefficients (r) with the ensemble mean fingerprint across the 30 ensemble members, and large circles show the mean correlation coefficients [calculated using a Fisher's z transform; see Lovenduski et al, 2021] for each COVID-like emissions scenario. For the model sampled at Mauna Loa, the mean correlation coefficient for the COVID-like ensemble is 0.4 with a wide range; stronger emissions reductions increase the mean correlation coefficient and narrow the range (subplot in Figure 1a), suggesting a higher probability of detecting the fingerprint from a single ensemble member or hypothetical observational record under higher emissions reductions.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 3 ensembles span 2019-2040 and consist of 30 members each that are forced with COVID-like CO2 emissions reductions beginning in December 2019 and resolving in December 2021; peak emissions reductions of 25% (COVID-like), 50% (2 × COVID-like), and 100% (4 × COVID-like) occur in May 2020 (Figure S1b). Hereafter, we refer to these later three ensembles collectively as the CanESM5-COVID ensemble, as described in Fyfe et al [2021] and Lovenduski et al [2021]. The CO2 emissions in the historical and control ensembles have spatial and seasonal variability; emissions are highest near urban centers in the Northern Hemisphere (Figure S2a) and peak in boreal winter when energy consumption in the Northern Hemisphere is at a maximum (Figure S2b).…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation